The Entry Mathematics Performance of the Bachelor of Science in Industrial Technology in Ilocos Sur Polytechnic State College - De La Cruz, J L (KnE Social Sciences, 2018)
Mathematics is an interesting but a very challenging subject. Several studies reported different factors which lead to students’ poor performance in this subject. This study generally aimed to assess the entry mathematics performance of the Bachelor of Science in Industrial Technology. Specifically, the study aimed to determine the influence of the student’s profile, attitudes and beliefs towards mathematics and the student’s impression to mathematics teachers towards their entry mathematics performance. It employed the descriptive-correlational research design. The findings revealed that the level of the entry mathematics performance of the students was good. It was disclosed that students have a positive attitude and beliefs towards Mathematics and impressions to Mathematics teachers. Students who have shown positive attitude, beliefs and impressions to Math teachers tend to perform better. Hence, performance in Mathematics can be improved by developing a positive attitude and beliefs of students towards the subject. Keywords: Industrial Technology, Intervention Plan, ISPSC, Mathematics Performance